Functional and Respiratory Capacity of Patients with Chronic Kidney Disease Undergoing Cycle Ergometer Training during Hemodialysis Sessions: A Randomized Clinical Trial - Antonio de Olival Fernandes; Yvoty Alves dos Santos Sens; Vivian Bertoni Xavier; Luiz Antonio Miorin; Vera Lúcia dos Santos Alves (International Journal of Nephrology)
Purpose. Exercise is recommended for patients undergoing hemodialysis, to reduce the decrease in functional capacity secondary to the progression of chronic kidney disease. A cycle ergometer can be easily added to an exercise routine during hemodialysis sessions. The purpose of this article was to assess the results of a training protocol with the cycle ergometer during hemodialysis sessions on the respiratory function and functional capacity of patients with chronic kidney disease on hemodialysis. Method. In this randomized clinical trial (NCT no. 02834026), 39 patients undergoing hemodialysis were randomly allocated into two groups: the treatment group (TG, n = 20), who underwent a cycle ergometer protocol training, and the control group (GC, n = 19), not trained. The TG attended 24 training sessions, three times a week, during the intradialytic period. Training intensity was aimed at keeping the heart rate between 50 and 70% of its maximum. All participants were evaluated before and after the eight consecutive weeks of follow-up and had biochemicals data, anthropometric, functional, and respiratory outcomes evaluated. Results. A significant difference was observed between groups in forced vital capacity, forced expiratory volume in the first second, peak expiratory flow, maximal inspiratory and expiratory pressure, and Borg score and distance covered in the six-minute walk test. Improvement was also observed in biochemical and Kt/V test results for the TG. Conclusion. The systematic training regimen with a cycle ergometer resulted in benefits in the respiratory function and functional capacity in patients with chronic kidney disease undergoing hemodialysis.